2018
DOI: 10.14419/ijet.v7i4.35.22342
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Individuals’ Acceptance of IOT-based Technologies

Abstract: This paper primarily aims to provide a systematic review of factors influencing the individuals’ acceptance of Internet of things (IoT). There are numerous studies in literature that examine factors affecting technology acceptance.  However, the studies on the review for acceptance of Internet of Things is limited.   This study conducted a review and analysis of 32 articles from academic journals and conference proceedings published about the adoption, acceptance and diffusion of IoT. According to the review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Another significant problem is the high implementation costs associated with blockchain networks [17][18][19]. To achieve data integrity and enhanced protection as well as to remove the need for a trustworthy intermediary, new expensive hardware is needed, such as custom information and communications technology equipment and applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another significant problem is the high implementation costs associated with blockchain networks [17][18][19]. To achieve data integrity and enhanced protection as well as to remove the need for a trustworthy intermediary, new expensive hardware is needed, such as custom information and communications technology equipment and applications.…”
Section: Discussionmentioning
confidence: 99%
“…Both the administrative and legal realms pose challenges to the acceptance and adoption of the technology. Public interest in energy markets is encouraged by regulatory authorities [19,21,29,36]. Blockchain systems have started to show promise in decentralized microgrids, but they face difficulties in aligning with central commands and grid coordination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other energy sources, such as concentrated solar energy, flywheel, dedicated battery, and hydro-pumped storage systems, are some of the technologies that have been utilized. Smart meters, wireless sensors, advanced communication, and power converters are some of emerging technologies in the industry [28][29][30][31][32].…”
Section: Technological Infrastructurementioning
confidence: 99%
“…Through an analysis of the studies reported in literature reviews (e.g. Alkawsi and Ali, 2018; Buchanan et al , 2015; Darby, 2010; Jaramillo et al , 2014; van de Kaa et al , 2019; Yang et al , 2019) and smart meter acceptance studies conducted worldwide (e.g. Bugden and Stedman, 2019; March et al , 2017; Park et al , 2014), it is noted that there is a lack of studies considering international results to consistently understand the effects of the various factors that determine the acceptance of smart meters by residential customers.…”
Section: Introductionmentioning
confidence: 99%